1998
DOI: 10.2527/1998.76112779x
|View full text |Cite
|
Sign up to set email alerts
|

Activation state of muscle satellite cells isolated from steers implanted with a combined trenbolone acetate and estradiol implant.

Abstract: Muscle satellite cells were isolated from seven yearling steers implanted for 31 d with a combined implant that contained 120 mg of trenbolone acetate (TBA) and 24 mg of estradiol (E2) and from seven nonimplanted, control steers. Implanted steers had a 28% greater ADG and a 23% greater feed efficiency than did nonimplanted steers. Implanted steers had increased (P<.001) circulating IGF-I concentrations on d 6, 14, and 31 after implantation, and circulating IGF-I concentrations in control steers remained consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 26 publications
4
66
1
1
Order By: Relevance
“…This difference may be due to either a difference in plating efficiency/cell survival within the first days after seeding the cells or may be an indication of the SCs responding at a different rate to seeding and medium -giving rise to a lag period before proliferation starts. A lag phase has been observed by others, with a difference in the length of the lag phase dependent on whether or not cattle were implanted with a trenbolone acetate/estradiol implant before isolation of SC (Johnson et al, 1998). Also SCs isolated from rats at different ages exhibit various lengths of the lag period before proliferation starts (Schultz and Lipton, 1982).…”
Section: Discussionmentioning
confidence: 92%
“…This difference may be due to either a difference in plating efficiency/cell survival within the first days after seeding the cells or may be an indication of the SCs responding at a different rate to seeding and medium -giving rise to a lag period before proliferation starts. A lag phase has been observed by others, with a difference in the length of the lag phase dependent on whether or not cattle were implanted with a trenbolone acetate/estradiol implant before isolation of SC (Johnson et al, 1998). Also SCs isolated from rats at different ages exhibit various lengths of the lag period before proliferation starts (Schultz and Lipton, 1982).…”
Section: Discussionmentioning
confidence: 92%
“…Hormone implants are considered the single best management tool to improve feed efficiency and average daily gain in beef cattle (Wileman, 2009;Hermesmeyer, 2000;Johnson, 1998;Lawrence, 2007). Hormones were first researched in food animal production systems in 1947 with the advent of diethylestilbesterol (DES) and have been FDA approved for use orally in beef cattle production since 1954 (Raun, 2002) to increase feed utilization, stimulate growth, and increase leanness of the animal.…”
Section: Hormone Implants In Feedlot Cattlementioning
confidence: 99%
“…It is imperative to improve cattle growth efficiency and decrease the time to get animals to market. One particular technology, hormone implants, have been FDA approved for use in beef cattle production since 1957 (Raun, 2002) and are considered the single best management tool to improve feed efficiency and average daily gain in beef cattle (Wileman, 2009;Hermesmeyer, 2000;Johnson, 1998;Lawrence, 2007). The use of hormonal implants in cattle improve ADG, DMI, HCW and lower feed-to-gain ratios when compared to non-implanted cattle (Reinhardt, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Androgenic and estrogenic implants are widely used, both individually and in combination, as growth promoters for cattle (Hayden et al, 1993;Johnson et al, 1996). Also, it was shown that artificial implantation of growth hormones increased the number of satellite cells (Johnson et al, 1998). Additionally, a number of studies in humans and animals have shown that hormone treatment increases the muscle fiber diameter.…”
Section: Introductionmentioning
confidence: 99%